Journal of Civil Engineering and Management: contribution to development and application of MCDM methods in construction management - Kapliński, Oleg; Vilutienė, Tatjana (Journal of Civil Engineering and Management, 2025)
Multi-criteria decision-making (MCDM) methods have improved considerably since the 1970s and are applied in many fields, demonstrating that the field of decision research remains important and valuable. Multi-criteria methods contribute to the research in civil engineering and construction management by identifying the optimal alternatives considering conflicting objectives. Researchers are applying MCDM methods in specific areas of civil engineering to resolve conflicts between economic, environmental and technological criteria. On the occasion of the 80th birthday of Prof. E. K. Zavadskas and 30 years of the Journal of Civil Engineering and Management (JCEM), this article aims to summarize the performance indicators of JCEM and its contribution to the development and application of MCDM methods in construction management. The journal’s performance indicators are outlined using bibliometric analysis.